The Implementation of the Independent Curriculum in ISMUBA Learning - Wicak Ramadhani; Tumin Tumin (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The curriculum is a learning guideline designed to fulfill student education at every school in Indonesia, which aims to create orderly learning and lead to the desired learning outcomes. The function of the curriculum includes organizing, structuring, and designing learning so that it runs effectively and efficiently in the process of learning and teaching in class and out of class. This study aims to understand the preparation, strategies, and factors influencing the implementation of the independent Curriculum at SMP Muhammadiyah Al-Mujahidin, Wonosari. The research method used is descriptive qualitative, with data collection techniques such as interviews, observations, and documentation. The participants included three teachers, a vice principal, a principal, and two students. The data was analyzed using Miles and Huberman's theory, which covers data collection, data reduction, and conclusion. The results of the study show that: 1) The preparation for implementing the curriculum includes the formation of a committee and training through the Ministry of Education and Culture, as well as In-House Training (IHT). 2) The strategies for implementation include the role of the school principal, phased implementation of the curriculum, student assessment, the use of differentiated learning strategies, and the development of students' hard skills. 3) The factors influencing the implementation of the curriculum are school facilities and teacher motivation.